MODEL FOR THE DEVELOPMENT OF GRAPHIC COMPETENCE OF STUDENTS OF THE ENGINEERING DIRECTION - Aralov Muzaffar Muxammadiyevich (Scholar Express Journal, 2022)
In modern conditions, higher educational institutions are aimed at the development and formation of students' social abilities, since this is the preparation of students for the life of society. The future specialist should be able to independently model the prospects of his life path, design future professional activities
Keywords: higher educational institutions, life of society